Pharmacological properties of biologically active substances of hops (Humulus Lupulus) - Nosalska, Tetyana; Dovha, Inna; Martynov, Artur; Kazmirchuk , Viktor; Batrak, Olena (Annals of Mechnikov's Institute, 2023)
In recent years, medicinal products of plant origin are gaining more and more popularity in the treatment of many diseases. Due to the presence in plants of many active substances with various pharmacological effects, it is possible to use herbal preparations for the treatment of many diseases. Medicinal products of plant origin have a wide spectrum of pharmacological action. Common hops are widely used in the treatment of insomnia and nervous disorders, as well as in diseases of some parts of the gastrointestinal tract. 23 aromatic compounds were found in the essential oil of hop cones, as well as sulfur-containing compounds. The hypnotic and sedative properties of hop cones are widely known. Thus, in an experiment on male rats, it was shown that the administration of the extract of hop cones in doses of 50 and 100 mg/kg showed a pronounced sedative effect, which exceeds the effect of diazepam. The hypnotic properties of hops have been experimentally confirmed in various types of animals: rats, mice, pigeons, and dogs. But regarding the sedative effect of hops, conflicting results have been obtained. Obviously, this is related to the low stability of biologically active substances in the process of storage and processing of raw materials. A pharmacological study of a number of biologically active substances of hops (essential oil, sodium lupulinate, hop extract and its mixture with valerian dialysate) showed that with an increase in their dose, a narcotic state is observed, a decrease in pain reflexes, a decrease in the threshold of pain sensitivity, followed by paralysis and animals . The hypnotic effect is manifested in a dose of 0.004 mg/g of animal weight. When studying the sedative and hypnotic effect of different fractions of the extract of hop cones and purified individual compounds, it was established that the neurotropic activity of hop preparations is due to the content of 2-methyl-3-buten-2-ol in them, which is structurally similar to a known synthetic compound with a hypnotic effect - Methylpentinol. In tests on rats, 2-methyl-3-buten-2-ol was not inferior to the synthetic analogue in terms of pharmacological activity. The anti-inflammatory activity of hop essential oil is mainly dependent on humulone, which has been shown to be a potent inhibitor of cyclooxygenase-2 (COX-2) expression through interaction with NFκB, leading to pronounced anti-inflammatory activity. α-humulene, administered either orally or as an aerosol, demonstrated marked anti-inflammatory properties in a murine model of allergic airway inflammation, an effect that was likely mediated through reduction of inflammatory mediators, adhesion molecule expression, and activation of transcription factors. The antioxidant properties of essential oil and other components of hops are known. Most hop polyphenols show lower or higher activity. In contrast, the antioxidant properties of terpene compounds can vary; the same compound may behave neutrally, exhibit relatively strong antioxidant properties, or, in many cases, may also act as a pro-oxidant. Antioxidant effects were also confirmed by different methods for other minor monoterpene hydrocarbons found in hops, such as β-pinene and γ-terpinene, which at concentrations between 50 and 1000 μg/ml showed different effects using the β-carotene/linolenic acid assay. acid and the DPPH method. The sesquiterpene carbohydrates α-humulene and β-caryophyllene are one of the most important components of hop essential oils. The antibacterial activity of hops, mainly against Gram-positive bacteria, has been known for many years and is well documented. A significant amount of research mainly points to a high antibacterial potential against gram-positive bacteria, whether it is hop extracts rich in prenylated acylphloroglucins and chalcones, or hop essential oil obtained from different varieties. According to the literature, extracts rich in essential oils are less active than extracts rich in prenylated acylphloroglucins, but little or moderate activity of hop essential oil against some Gram-negative bacteria such as Escherichia coli and Yersinia enterocolitica was observed. The selectivity and efficacy of hop extracts rich in prenylated phenolic compounds against strains of Gram-positive bacteria associated with human health, including Staphylococcus, Streptococcus, Micrococcus, and Mycobacterium strains, have been demonstrated. Some studies have also focused on human pathogenic bacteria frequently found in the biomedical and food industries, such as Clostridium botulinum and Listeria monocytogenes. The antibacterial activity of hops is mainly attributed to bitter acids, particularly α-acids and β-acids, which also have antifungal activity. The antibacterial potential increases due to the degree of hydrophobicity of acylphloroglucins. The number and length of acyl or prenyl side chains have a positive effect on the antibacterial effect. Thus, the effectiveness decreases as follows: β-acids (lupulone), α-acids (humulone), iso-α-acids (isohumulone). Lupulone also showed significant antibacterial activity against several gram-negative Helicobacterpylori bacteria, including resistant strains. Thus, the biologically active substances of hops determine the entire breadth of its pharmacological activity. Keywords: hops, Humulus Lupus, biologically active substances, pharmacological properties